Three-dimensionally integrated trace fossils from shallow-marine deposits in the Lower Cretaceous of the Neuquén Basin (Argentina): Hillichnus agrioensis isp. nov. - Pazos, Pablo Jose (2010)
A complex trace fossil that requires a three-dimensional (3D) reconstruction is described and interpreted. The specimens studied are assigned to a new ichnospecies (Hillichnus agrioensis) of Hillichnus Bromley et al., 2003. Most of them are uncollectable and a compound iconotype was designed to characterise the new ichnospecies. The three-dimensional trace fossil has been recorded in marginal-marine deposits close to the top of the Agrio Formation (Lower Cretaceous of Neuquén Basin, Argentina). The new ichnospecies shows a different pattern of feeding than H. lobosensis Bromley et al., 2003, and records defaecation downward in the deeper preservational level (level 4). Feather-like structures (level 2) that typify the ichnogenus also record the activity of an inhalant siphon and indicate a retractile movement. The vertical shafts (level 1) are scarcely recorded. Aligned double rings also document the infaunal habit of the tellinid bivalves that are considered the most likely producers of the trace. It is clear that when only level 2 is exposed, in some cases this form can be assigned to Jamesonichnites heinbergi Dam 1990a consequently, this ichnospecies is interconnected with more than one ichnogenus. Vertical projections recorded in branches differ from the type ichnospecies H. lobosensis Bromley et al., 2003. The occurrence in marginal-marine facies is congruent with the record of Jamesonichnites but not common in the type species and similar to those more frequent in deep-sea deposits (e.g. Polykampton alpinum Ooster, 1869).